The MRC1/CD68 ratio is positively associated with adipose tissue lipogenesis and with muscle mitochondrial gene expression in humans. - José María Moreno-Navarrete (PLoS ONE, 2013)
BACKGROUND: Alternative macrophages (M2) express the cluster differentiation (CD) 206 (MCR1) at high levels. Decreased M2 in adipose tissue is known to be associated with obesity and inflammation-related metabolic disturbances. Here we aimed to investigate MCR1 relative to CD68 (total macrophages) gene expression in association with adipogenic and mitochondrial genes, which were measured in human visceral [VWAT, n = 147] and subcutaneous adipose tissue [SWAT, n = 76] and in rectus abdominis muscle (n = 23). The effects of surgery-induced weight loss were also longitudinally evaluated (n = 6). RESULTS: MCR1 and CD68 gene expression levels were similar in VWAT and SWAT. A higher proportion of CD206 relative to total CD68 was present in subjects with less body fat and lower fasting glucose concentrations. The ratio MCR1/CD68was positively associated with IRS1gene expression and with the expression of lipogenic genes such as ACACA, FASN and THRSP, even after adjusting for BMI. The ratio MCR1/CD68 in SWAT increased significantly after the surgery-induced weight loss (+44.7%; p = 0.005) in parallel to the expression of adipogenic genes. In addition, SWAT MCR1/CD68ratio was significantly associated with muscle mitochondrial gene expression (PPARGC1A, TFAM and MT-CO3). AT CD206 was confirmed by immunohistochemistry to be specific of macrophages, especially abundant in crown-like structures. CONCLUSION: A decreased ratio MCR1/CD68 is linked to adipose tissue and muscle mitochondrial dysfunction at least at the level of expression of adipogenic and mitochondrial genes.